Ketidakefektifan Pola Nafas Pada Pasien Tn. M Dengan Chronic Kidney Disease (CKD) Di Ruang Igd Rs Gunung Jati Kota Cirebon - Dewi Oktoviani; Erida Fadila; Evi Nurmala Fia; Kiki Ameliya; Rizal Nova Jalaludin (Awatara Publisher, 2024)
Chronic kidney disease can cause pulmonary edema, making it difficult for patients with CKD to breathe normally. Nonpharmacological measures that can be taken are teaching deep breath relaxation techniques that aim to increase alveoli ventilation and reduce the work of breathing. The purpose of this study was to provide an overview of nursing care for patients Mr. M with chronic kidney disease in the emergency room of Gunung Jati Hospital, Cirebon City. M with chronic kidney disease in the emergency room of Gunung Jati Hospital, Cirebon City. This type of research uses case studies. Data collection techniques were carried out by interview, observation, and study of medical record documentation. Data analysis in this case study was carried out descriptively including assessment, diagnosis, intervention, implementation, and evaluation while the patient was in the emergency room. Management of deep breath relaxation techniques, monitoring respiration and monitoring oxygen saturation carried out during patients in the emergency room can affect the improvement of the patient's tightness condition as evidenced by decreased dyspnea, improved breathing frequency, and improved oxygen saturation. It is hoped that patients can carry out the diets given and families provide support during the treatment process to improve the patient's quality of life